Show me the magic - Mazursky, Paul. (New York Simon & Schuster, 1999)
Paul Mazursky--writer, film director, actor, and producer--has created a body of work over the past thirty years that has established him as one of America's most respected and admired filmmakers. His films are often personal, intimate, and humorous observations of the human condition.
CMC-2846 donated by Mr. Gino Dormiendo.
Keywords: Mazursky, Paul; Motion picture producers and directors -- United States -- Biography